AKSES MENDAPATKAN KEADILAN (ACCESS TO JUSTICE) DALAM KONSTITUSI INDONESIA - Julaiddin Julaiddin (LPPM Universitas Ekasakti Padang, 2019)
Through the law, the state provides facilities for correct activities. The law must guarantee the creation of social justice for all Indonesian people. The inauguration of Indonesia as a state of law in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia is mutatis-mutandis (the Government) is responsible for ensuring that every citizen is treated equally in the eyes of the law (justice for all), as well as the guarantee of every citizen to get access to justice (access to justice), which is mandated by the constitution. This research is focused on the concept of access (justice) to get justice in the Indonesian constitution. This study uses a normative juridical approach, the analysis used is descriptive qualitative with secondary data sources. The conclusion is that law enforcement officials such as the police, prosecutors, and judges as institutions whose functions are related to law enforcement and justice must be able to realize the Indonesian legal state through a fair legal process, as a reality, and not law enforcers who use their power arbitrarily. the authority that is contrary to the 1945 Constitution.